Utilization of Satellite Imagery for Mapping the Distribution of Seagrass on Buhung Pitue Island - Rosalina, Dwi; Arafat, Yasser; Wahda, A Nurtasya; Rombe, Katarina Hesty; Khasanah, Ruly Isfatul; Sofarini, Dini (Indonesian Journal of Geography, 2024)
Buhung Pitue Island has seagrass beds those which are spread almost evenly along its coast. Research using remote sensing technology in an effort to support seagrass conservation in Indonesia needs to be carried out. Spatial data is relatively easy to obtain because there are many types of images with various spatial resolutions. The image can be obtained on google earth. Analysis of the distribution of seagrass areas was obtained by digitizing on screen in ArcGIS software, namely in seagrass areas where the boundaries are known. Digitizing is conducted by enlarging the seagrass area in the downloaded image, performing radiometric and geometric corrections, and digitizing to create a shapefile (shp) storing the location, shape, and attributes of geographic features. The seagrass distribution area of Buhung Pitue Island was of 36.5 Ha in 2014 and was of 39.6 in 2021. The rate of change in area from 2014 to 2021 was of 0.085% (an increase of 3.1 ha). The distribution area of seagrass has increased due to natural factors and restrictions on human activities during the COVID-19 pandemic. In addition, another factor supporting the increase in seagrass distribution is the abundance of Enhalus acoroides seagrass species growing and spreading over long distances. The sea surface temperature was high, which was 30.37 °C, while the current speed was categorized as slow because it was around 0.01 m/s. Although the results are obtained from high-resolution imagery, an accuracy test still needs to be conducted.